Impact of the COVID-19 pandemic on surgical site infections: a multi-center study evaluating incidence, pathogen distribution, and antimicrobial resistance patterns - Şiran Keske; Elif Sargın Altunok; Emel Azak; Ezgi Gülten; Tuğba Arslan Gülen; Çiğdem Ataman Hatipoğlu; Ali Asan; Derya Korkmaz; Bahar Kaçmaz; Yeşim Kızmaz; Ayşe Batırel; Fethiye Akgül; et al. (Antimicrobial Resistance and Infection Control)
Abstract Background Surgical site infections (SSIs) are among the most significant concerns in healthcare settings, presenting challenges in patient management and healthcare outcomes. The emergence of the COVID-19 pandemic has further complicated the landscape of infectious disease epidemiology, impacting the distribution and resistance characteristics of pathogens responsible for SSIs. Understanding these dynamics is essential for improving infection prevention and treatment strategies. Methods This retrospective multi-center study included 17 hospitals in Turkey, analyzing SSI cases from January 2019 to January 2023. The study was divided into three phases: pre-pandemic (January 2019 - March 2020), early pandemic (March 2020 - January 2022), and late pandemic (January 2022 - January 2023). We assessed demographic and clinical characteristics, pathogen distributions, and resistance rates, focusing on multidrug-resistant (MDR) pathogens. Results A total of 2,058 patients with SSIs were included. The SSI rate increased from 0.79% in 2019 to 0.87% in 2020, then decreased to 0.46% in 2021 and 0.50% in 2022. The most prevalent pathogens were E. coli (21.9%) and K. pneumoniae (14.6%). Resistance to meropenem in K. pneumoniae rose from 23% pre-pandemic to 33% post-pandemic, while ceftazidime-avibactam resistance surged from 6 to 43%. P. aeruginosa showed increased quinolone resistance from 18 to 27%, with colistin resistance rising to 13% in the late pandemic phase. Conclusions This study highlights the significant impact of the COVID-19 pandemic on SSIs in Turkey, revealing concerning trends in antibiotic resistance among key pathogens. Ongoing surveillance and enhanced infection control measures are essential to address these challenges and improve patient outcomes in the post-pandemic era.